Design Features of Embodied Conversational Agents in eHealth: a Literature Review. Issue 138 (June 2020) - ter Stal, Silke; Kramer, Lean Leonie; Tabak, Monique; op den Akker, Harm; Hermens, Hermie
Abstract: Embodied conversational agents (ECAs) are gaining interest to elicit user engagement and stimulate actual use of eHealth applications. In this literature review, we identify the researched design features for ECAs in eHealth, the outcome variables that were used to measure the effect of these design features and what the found effects for each variable were. Searches were performed in Scopus, ACM Digital Library, PsychINFO, Pubmed and IEEE Xplore Digital Library, resulting in 1284 identified articles of which 33 articles were included. The agents speech and/or textual output and its facial and gaze expressions were the most common design features. Little research was performed on the agent's looks. The measured effect of these design features was often on the perception of the agent's and user's characteristics, relation with the agent, system usage, intention to use, usability and behaviour change. Results show that emotion and relational behaviour seem to positively affect the perception of the agents characteristics and that relational behaviour also seems to positively affect the relation with the agent, usability and intention to use. However, these design features do not necessarily lead to behaviour change. This review showed that consensus on design features of ECAs in eHealth is far from established. Follow-up research should include more research on the effects of all design features, especially research on the effects in a long-term, daily life setting, and replication of studies on the effects of design features performed in other contexts than eHealth.